Cytotoxicity, in vitro models and preliminary in vivo study of dual physical and chemical gels for endovascular embolization of cerebral aneurysms. Issue 9 (28th January 2013) - Bearat, Hanin H.; Preul, Mark C.; Vernon, Brent L.
Abstract : We report the evaluation of dual‐gelling poly( N ‐isopropylacrylamide)‐based polymer systems as embolic agents for intracranial aneurysms. These hydrogels undergo gelation physically via temperature‐responsiveness of poly(NIPAAm) and chemically through a Michael‐addition reaction between thiol and vinyl functional groups on the copolymers. Cytotoxicity studies were performed for biocompatibility of the hydrogels. In vitro glass models were utilized to assess injectability and embolization using the gelling systems and an in vivo swine model was used as proof‐of‐concept for catheter delivery, injection, and occlusion properties of the hydrogels. Rheology creep tests were conducted for determination of viscoelastic behavior, and degradation of the hydrogels was also investigated. Live/dead and proliferation assays indicated good biocompatibility of the hydrogels. In vitro and in vivo assessment demonstrated that the hydrogels were easily delivered via catheters into the aneurysms. Slight recanalization was observed in vivo, with some adhesion of the gels to the balloon catheter seen in vitro . The materials show creep deformation occurring with time; however, the hydrogels did not degrade over the course of 1.5 year. With the possibility to engineer hydrogels bottom‐up for particular applications, these studies show properties that need to be optimized for dual‐gelling polymer systems to serve as liquid‐to‐solid embolic agents for aneurysm treatment. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2515–2525, 2013.